Validation of a German version of the International Hip Outcome Tool (G-iHOT33) according to the COSMIN checklist: how much improvement is clinically relevant? - Baumann, Florian; Fickert, Stefan (Archives of orthopaedic and trauma surgery, 2016)
Purpose: The evaluation of the subjective health-related quality of life is especially for young, active patients with hip joint disorders important. The MAHORN study group has recently developed the “International Hip Outcome Tool” (iHOT33), a self-administered patient-reported outcome tool, which includes questions on the patient’s symptoms, functional and sports limitations as well as social, emotional, and occupational limitations. The purpose of this study was to adapt and validate a German version of the iHOT33 according to the COSMIN checklist. Methods: To validate the G-iHOT33, we conducted a prospective multicenter cohort study on patients with hip disorders and a score ≥4 on the modified Tegner Activity Scale. The patients completed the G-iHOT33 questionnaire twice at intervals of at least 2 weeks. In addition, we recorded the Hip Outcome Score (HOS), a modified Tegner Activity Scale (TAS), the EuroQol-5D (EQ5-D), and a subjective assessment of the limitations. Evaluation of psychometric properties was conducted following the COSMIN checklist for validation of health status measurement instruments. The methodical testing for reliability included internal consistency, test-retest reliability, and measurement error. For testing of validity, we analyzed construct validity, hypotheses testing, interpretability, and responsiveness. Results: Between December 2013 and December 2014, eighty-three consecutive patients completed both questionnaires and were available for data analysis. Cronbach’s α was 0.97 (95 % CI 0.96, 0.99) confirming internal consistency and test-retest reliability of the G-iHOT-33 was high with an ICC = 0.88 (95 % CI 0.80, 0.99). All a priori hypotheses were confirmed, further, no floor- or ceiling-effects occurred. The G-iHOT33 showed good responsiveness with a minimal important change (MIC) of 10 points. Conclusions: The German translation of the iHOT-33 (G-iHOT-33) is a viable tool for the evaluation of active patients with a hip disorder. Following the complete COSMIN checklist, we could prove that G-iHOT33 is a reliable, valid, and responsive PRO measurement tool. We could show that the minimal important change, a change of health condition the patient discerns is 10 points in the G-iHOT33 scale. This is the first study providing results on psychometric properties of the iHOT33 subscales. Level of evidence 1b validating cohort study.